Profile of Cooperation Ability in Fourth Grade Students in Learning Entrepreneurship at Brecong 2 State Elementary School - Kurnianto, Rizki; Fatimah, Siti (Universitas Sebelas Maret, 2019)
The purpose of this study is to describe the profile of students' cooperative skills in entrepreneurial learning. This research approach is a qualitative approach and type of descriptive research. The subjects of this study were the fourth grade students of Brecong State Elementary School 2 Academic Year 2019/2020. The object of this study is the ability of students to collaborate in learning entrepreneurship. Data analysis was performed using descriptive techniques and existing data in the form of qualitative data from the observation sheets and student questionnaires, which were then described. The results showed that overall the ability of students to collaborate in learning entrepreneurship with